The Recovery of Debts Inherent in Cheques without Cover in Cameroon via the OHADA Simplified Recovery Procedure and Enforcement Measures - Penda, Akama Samuel; Ndikum, Nji Keneth (International Journal of Trend in Scientific Research and Development, 2019)
The vast number of commercial transactions that take place daily in the modern business world will be inconceivable without negotiable instruments like cheques. This is the reason why the recovery of debts inherent in cheques without cover has been given the attention it deserves within the CEMAC Region under the OHADA Uniform Act on Business Law. The OHADA Uniform Act on Simplified Recovery Procedure and Enforcement Measures has instituted a procedure in the member states of the OHADA zone to recover debts of a company when it eventually goes bankrupt or when it winds up. It should however be understood that all the member states of CEMAC are OHADA signatories. This ipso facto means that Cameroon being a member of CEMAC, with its bi jural nature, where the Common Law and Civil law legal systems operates in the Former West Cameroon and Former East Cameroon respectively, both parts of the country are bound to implement the OHADA Uniform Act in their various jurisdictions. The Uniform Act on Simplified Recovery Procedures and Enforcement Measures was issued on the 10th of April 1998. Like the Uniform Act on Securities, this Act overlaps the bound of pure business law in that it effects a general reform of civil procedure in relation to recovery and enforcement. The reform was indispensable of the OHADA Member States, only Mali had, in 1994, put in place a modern system that was suited to present day economic and social conditions. Otherwise, the relevant legislation dated, at best from the 1970s and in several cases from colonial times. The OHADA Uniform Act governs commercial companies and Economic Interest groups. Since banks are commercial companies governed under Public Limited Companies S. As , they are equally governed by the OHADA Uniform Act. Thus, this paper questions the potentials of the OHADA Simplified Recovery Procedure and Enforcement Measures in relation to the special mechanisms for the Recovery of Debts inherent in cheques without cover in Cameroon.
Keywords: Chèques; Procédure simplifiée; Recouvrement de créances; Recovery of Debts; Voies d'exécution

Recognition and enforcement of foreign judgments : proposals for OHADA - Kazadi, Nshingu (University of Johannesburg, 2017)
LL.M. (International Commercial Law) Please refer to full text to view abstract

A Standing Question: Mortgages, Assignment, and Foreclosure - Zacks, Eric A; Zacks, Dustin A (The Journal of Corporation Law, 2015)
“Banks are neither private attorneys general nor bounty hunters, armed with a roving commission to seek out defaulting homeowners and take away their homes in satisfaction of some other bank’s deed of trust.” This Article examines the judicial treatment of mortgage assignments across various jurisdictions in the foreclosure context. Although some courts do permit debtors to challenge suspicious or problematic assignments, most have ignored such problems and denied standing to debtors attempting to assert assignment-based defenses. This is particularly surprising given the widespread and well-documented problems with foreclosure “robo-litigation,” including backdated documents, fraudulent notarizations, and unauthorized signatures. Despite the abuse of process by foreclosing entities, courts have permitted foreclosures to continue unabated and, in some instances, have even precluded the possibility of discovery to debtors seeking to ensure that title and assignments are legally valid. Judicial ambivalence about formal compliance by mortgage assignors and assignees in the foreclosure context is somewhat ironic given most courts’ routine enforcement of instruments against debtors who do not formally comply with all contractual terms. Current adjudicative approaches to mortgage assignment are seemingly disconnected from the devastating reality of the home mortgage crisis and its causes. Moreover, there are several rationales that would support a more robust enforcement of technical compliance with assignment procedures, including the need for procedural equity, title certainty, and public records integrity. Thus, as evidence exists that banks are still making many of the same problematic mistakes regarding transfer documentation, courts can perform an essential monitoring role as an important spur towards reform. Although it would not address all of the underlying causes of the housing crisis, an adjudicative approach that liberally permits challenges to mortgage assignments would encourage lenders and servicers to be more circumspect in their foreclosure processes.

A Proposed discharge dispensation for consumer debtors in Tanzania - Maghembe, Ngwaru Jumanne (University of Pretoria, 2013)
The Tanzanian private sector is growing, partly due to the state’s efforts to conform to the global economy. As the economy expands and the National Microfinance Policy of 2001 is realised, more and more credit has been made available to consumers. As a direct consequence of the increase of credit, the number of over- indebted consumers in Tanzania is on the rise. The current debt relief system is regulated by the Tanzanian Bankruptcy Act no. 9 of 1930, a piece of colonial legislation. Unfortunately this law is ineffective, costly and outdated. Some of the problems identified in this study with this debt relief regime include the lack of a cost- effective alternative to bankruptcy and its total reliance on the judiciary, an institution that is itself overburdened and requires reform. The purpose of this study is to make recommendations for the reform of the current debt relief system and propose a debt relief dispensation for consumer debtors in Tanzania that will efficiently cure over- indebtedness. A wide comparative investigation was undertaken in this study of selected common law, civil and mixed legal systems that have substantial experience with the boom in over-indebted consumers now facing Tanzania. A number of solutions were borrowed from these systems that may potentially solve Tanzania’s debt relief problem. One of the main findings of this thesis is that, over time, developed jurisdictions that rely on credit in the private sector appear to be converging on the same type of procedures and moderate philosophies for consumer debt relief. These include less judicial supervision for debt relief procedures, less freedom of choice for over-indebted consumers when it comes to the type of procedures available, and mandatory surplus income repayments for debtors who can afford it. In order to address the problems of the Tanzanian debt relief system, this thesis proposes a complete overhaul of the administration of debt relief procedures in Tanzania and the introduction of a combined alternative to bankruptcy that consists of three joint procedures. A number of amendments are also proposed for the Bankruptcy Act no.9 of 1930. This thesis states the status of legal developments as they were in the selected jurisdictions on 31 December 2012.
Keywords: Bankruptcy Act; Current debt relief system; Tanzania